Enhancement of Factor VIII-von Willebrand Factor Ristocetin Cofactor Activity by Monoclonal Antibodies - Hornsey, V; Micklem, L R; McCann, M C; James, K; Dawes, J; McClelland, D B L; Prowse, C V (Thrombosis and Haemostasis, 1985)
Five monoclonal antibodies to human von Willebrand factor were selected for characterization from 18 produced in murine hybridomas. All showed a high and specific affinity for human von Willebrand factor (vWf) but exhibited little if any crossreaction with sera from other species. The antibodies defined four epitopes on vWf, none of which were involved in platelet binding. Binding of two distinct antibodies at one of these epitopes was associated with enhancement of the rate of vWf-dependent platelet agglutination in the presence of ristocetin. This effect was more noticeable when cryosupernatant plasma was used in place of normal plasma as the source of vWf, and was not explicable simply in terms of antibody-induced cross-linking of vWf.
Keywords: Factor VIII; von Willebrand factor; Ristocetin cofactor; Monoclonal antibody